Effect of Homocysteine Reduction by B-Vitamin Supplementation on Markers of Clotting Activation - Klerk, Mariska; Verhoef, Petra; Verbruggen, Bert; Schouten, Evert G.; Blom, Henk J.; Bos, Gerard M. J.; den Heijer, Martin (Thrombosis and Haemostasis, 2002)
Homocysteine may have an effect on risk of cardiovascular disease by stimulating procoagulant factors and/or impair anti-coagulant mechanisms or fibrinolysis. However, data in humans of such effects are sparse. In this intervention study, we examined the effect of homocysteine lowering by B-vitamin supplementation on prothrombin fragments 1 and 2 (F1+2), thrombin-antithrombin complex (TAT), and fibrin degradation products (D-dimer). The study comprised 118 healthy volunteers, 50 with homocysteine > 16 µmol/L and 68 with homocysteine ≤ 16 µmol/L, who were randomized to placebo or highdose B-vitamin supplements (5 mg folic acid, 0.4 mg hydroxycobalamin, and 50 mg pyridoxine) daily for 8 weeks. Although homocysteine concentrations were 27.7% (p < 0.0001) reduced in the Bvitamin group compared to the placebo group, no effect on F1+2 and TAT concentrations was observed. A 10.4% reduction was observed for D-dimer (p = 0.08).In conclusion, it appears that in healthy subjects homocysteine reduction by B-vitamin supplementation has a modest beneficial effect on clotting activation.
Keywords: Homocysteine; B-vitamins; clotting activation; intervention; healthy volunteers